POTENTIAL OF ELECTRONIC EDUCATIONAL RESOURCES IN THE FORMATION OF INFORMATION LITERACY OF STUDENTS - Rakhmatov Sanat Sultonovich (Modern American Journals, 2025)
The article highlights the possibilities of electronic educational resources in the formation of information literacy of students and their importance at present.
Keywords: Education, electronic resource, competence, tool, communication